Carbon intensive but decarbonising quickly? Retrospective and prospective life cycle assessments of South African pome fruit - de Kock, Lorren (Department of Chemical Engineering, 2019)
The South African economy has in the past been categorised as carbon intensive due to an energy and capital intensive development path and an associated set of economic activities termed the minerals-energy complex. International export markets, specifically the European Union (EU), are systematically applying pressure on imported products with a high carbon footprint through potential trade barriers, border tariffs and consumer lobbying. The objective of this research is to determine whether South African pome fruit has a higher global warming potential (GWP) per kg fruit compared to pome fruit cultivated and packaged in other countries. Following on from this finding, is to determine whether the Greenhouse Gas (GHG) emissions for pome fruit in South Africa are declining, ,as could be expected based upon the declining carbon intensity of the South African economy since 1990 and efficiency improvements in the industry itself. The Attributional Life Cycle Assessment (ALCA) methodology is used to determine the Global Warming Potential (GWP) per kg fruit for multiple boundaries within the value chain, retrospectively for the years 2000, 2010 and prospectively for 2020. The product system boundary includes the farm, packhouse, controlled atmosphere store (CA) and cold store (CS). For the Life Cycle Inventory (LCI), the temporal variations in pome fruit cultivation, packing and storing for the export and local market are taken into account for each of the years studied. Using the single issue characterisation methods – the GHG Protocol and the IPCC GWP 2013 100a – the results for each of the years under study are compared at a value chain, boundary and activity level. The results indicate that the baseline GWP result for South African pome fruit in the year 2000 was relatively high compared to similar international LCA research on apples and pears during this period. However, the results for the years 2010 and 2020 clearly indicate a sustained decline in relative GHG emissions of South African pome fruit according to the GWP indicator result per kg fruit and the normalised results for the industry. It is clear that there has been an increase in eco-efficiency in a number of farming and agro-processing practices since 2000 which correlates to the declining CO2e emissions in the boundaries and value chain of South African pome fruit. The carbon intensity and efficiency of the pome fruit value chain is also determined for each year using the kg CO2e per kg fruit and the industry revenue for a specific year (ZAR 2010 adjusted for PPI). The findings support the hypothesis that the carbon intensity of the pome fruit industry has indeed declined since the year 2000. This decline in carbon intensity represents a relative decoupling of CO2e emissions from economic growth of the industry from 2000 to 2020.